Multifunctional nanostructured metal oxides for energy harvesting and storage devices - Pawade, Vijay B.; Salame, Paresh H.; Bhanvase, Bharat A. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Metal oxide nanoparticles exhibit potential applications in energy and environmental fields, such as solar cells, fuel cells, hydrogen energy, and energy storage devices. This book covers all points from synthesis, properties, and applications of transition metal oxide nanoparticle materials in energy storage and conversion devices. Aimed at graduate-level students and researchers associated with the energy and environment sector, this book addresses the application of nontoxic and environmentally friendly metal oxide materials for a clean environment and deals with synthesis properties and application metal oxides materials for energy conversion, energy storage, and hydrogen generation.
Chapter 1 Synthesis, Properties, and Applications of Transition MetalOxide Nanomaterials--R. Rakesh Kumar, K. Uday Kumar, and D. HaranathChapter 2 Transition Metal-Oxide-Based Electrodes for Na/Li Ion Batteries--Paresh H. SalameChapter 3 Layered Metal Oxides/Hydroxides for High-PerformanceSupercapacitor--Deepa B. Bailmare, Chandrasekar M. Subramaniyam,and Abhay D. DeshmukhChapter 4 Transition Metal Oxide-Based Multiferroic Materialsfor Spintronics and Energy-Harvesting Applications--Rajan Singh and Jayant KolteChapter 5 Advanced Graphene-Transition Metal-Oxide-BasedNanocomposite Photocatalysts for Efficient Degradationof Pollutants Present in Wastewater--S. Raut-Jadhav and M. V. BagalChapter 6 Metal Oxides for High-Performance Hydrogen Generationby Water Splitting--Sagar D. Balgude, Shrikant S. Barkade,and Satish P. MardikarChapter 7 Electrocatalysts in Solid Oxide Fuel Cells--A. P. Khandale and S. S. BhogaChapter 8 Overview on Metal Oxide Perovskite Solar Cells--N. Thejo Kalyani and S. J. DhobleChapter 9 QDs for High Brightness WLEDs and Solar Cell Devices--Vijay B. Pawade, K. N. Shinde, and S. J. DhobleChapter 10 Metals, Metal Oxides, and Their Composites--Safetyand Health Awareness--Shrikaant KulkarniChapter 11 Future Scope of Various Nanostructured Metal Oxidesfor Sustainable Energy Sources--Jaykumar B. Bhasarkar, Bharat A. Bhanvase,and Vijay B. Pawade
OCLC-licensed vendor bibliographic record.
Keywords: Transition metal oxides; Nanoparticles; Energy harvesting; Energy storage; SCIENCE / Energy; TECHNOLOGY / Electricity; TECHNOLOGY / Material Science